Three Cases of Transtracheal Catheter Oxygenation for Postoperative Dyspnoea with Pituitary-Dependent Hyperadrenocorticism in Dogs Treated by Surgery. (22nd March 2022) - Tanaka, Sachiyo; Suzuki, Shuji; Teshima, Takahiro; Ishino, Hirokazu; Sato, Asaka; Kanno, Nobuo; Hara, Yasushi
Abstract : Transsphenoidal surgery (TSS) is a curative treatment for pituitary-dependent hyperadrenocorticism, and its use in dogs has recently increased. One of the most serious postoperative complications of TSS is dyspnoea. We report three cases where transtracheal catheter oxygen therapy prevented death from respiratory distress secondary to enlarged soft palate after TSS.